Inflammatory Pseudotumor of Spleen: A Case Report - Toumi, Omar; Ammar, Houssem; Chhaidar, Amine; Gupta, Rahul; Korbi, Ibtissem; Nasr, Mohamed; Noomen, Faouzi; Zouari, Khadija (Archives of Clinical and Medical Case Reports, 2017)
Introduction: Inflammatory pseudotumor (IPT) is a rare benign disease which presents as tumor like mass mimicking malignancy. The most common sites are lungs, liver, orbits and gastrointestinal tract. Splenic IPT is very rare. Presentation of Case: A 41-year-old woman presented with the complaints of left upper quadrant pain radiating to the back for a year. Abdominal ultrasound and computed tomography (CT) revealed a hypodense lesion of approximately 5 cm located in the splenic parenchyma near the hilum. Hydatid serology was negative. The patient was treated with splenectomy due to diagnostic dilemma and final diagnosis of IPT was made on histopathological examination of the resected spleen. Discussion: Splenic IPT usually affects middle aged women presenting as incidental finding on abdominal imaging. It is most often isolated but at times may be associated with IPT at other sites probably suggesting a systemic etiology. Radiological findings are non-specific leading to diagnostic dilemma. Splenectomy is useful for treating symptomatic cases and helps in making the accurate diagnosis in cases of diagnostic dilemma. Conclusion: Splenic IPT is a rare, benign condition which should be included in the differential diagnosis while evaluating a splenic mass.